Updates on brucellosis in Malaysia and Southeast Asia - Bamaiyi, Pwaveno Huladeino; Hassan, Latiffah; Bejo, Siti Khairani; Mohamed, Zainal Abidin (Department of Veterinary Services Malaysia, 2014)
Brucellosis has been in South East Asia for many generations affecting both man and animals and responsible for massive economic losses. The threat to the economy and to public health from this zoonotic disease is so great to ignore. Over the years there have been many attempts to control and possibly eradicate this infection but these efforts have not fully yielded the desired results due to many factors mentioned in this paper. Eradication, though expensive, actually saves a lot of economic resources when properly implemented. In this review, the past and current situation of brucellosis in South East Asia is explored with particular reference to Malaysia and challenges to the full eradication of the infection are elucidated.